1998
DOI: 10.1111/j.1524-4725.1998.tb04189.x
|View full text |Cite
|
Sign up to set email alerts
|

Mullerʼs Ambulatory Phlebectomy for Varicose Veins of the Foot

Abstract: The venous anatomy of the foot does not indicate major restrictions in the treatment of its varicosities. Ambulatory phlebectomy is the safest and most elegant treatment option for varicose veins of the foot. Venous surgery and sclerotherapy may be used successfully in special cases only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
(12 reference statements)
1
18
0
Order By: Relevance
“…It has proven to be a safe and effective therapy modality for varicose veins of most calibers. In a review of the literature we found that AMP can be used safely for varicose veins of the feet 1 . We have also demonstrated preliminary results of 14 treated patients in our clinic.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…It has proven to be a safe and effective therapy modality for varicose veins of most calibers. In a review of the literature we found that AMP can be used safely for varicose veins of the feet 1 . We have also demonstrated preliminary results of 14 treated patients in our clinic.…”
mentioning
confidence: 51%
“…AMP is also reported to enhance cosmetic appearance 1 . In 20% of the cases treated in our clinic, postoperative complications occurred and standard procedures were followed to deal with these problems.…”
Section: Discussionmentioning
confidence: 95%
“…All patients had miniphlebectomy with the Muller tech‐ nique 11 with a no. 11 scalpel with an average stitch length of 5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Regions particularly appropriate for ambulatory phlebectomy include the accessory saphenous veins of the thigh, groin pudendal veins, reticular varicose veins (popliteal fold, lateral thigh and leg), in particular if feeding telangiectasias (Fig. 4a–b), 20,21 veins of the ankles and the dorsal venous network of the foot 22–24 (Fig. 5a–b).…”
Section: Cosmetic Indicationsmentioning
confidence: 99%